Iron-based composite material and preparation method and application thereof
By electrochemically modifying micron-scale zero-valent iron particles and loading carbon materials to form iron-based composite materials, the problems of poor dispersion and easy agglomeration of zero-valent iron catalysts are solved, and their degradation ability and stability to groundwater pollutants are significantly improved.
Patent Information
- Application Number
- CN202311367057.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-20
AI Technical Summary
In the prior art, zero-valent iron catalysts have poor dispersion and are prone to agglomeration, and the repair performance of their repair materials to groundwater pollutants needs to be further improved.
By electrochemically modifying micron-scale zero-valent iron particles with metal sulfides and citrates and loading carbon materials on their surfaces to form iron-based composites to improve their dispersion, stability and degradation capabilities.
This method effectively improves the dispersion and stability of zero-valent iron, extends its effective cycle, and significantly improves the degradation ability of groundwater pollutants.
Smart Images

Figure BDA0004504695910000201 
Figure BDA0004504695910000211
Abstract
Description
Technical Field
[0001] The invention relates to the field of material preparation and organic pollution control, and in particular to an iron-based composite material and a preparation method and application thereof. Background Art
[0002] With the development of economy and society and the continuous acceleration of industrialization, organic pollution of soil and groundwater has become a global environmental problem. Due to the complex environment of soil and groundwater, once polluted, it takes several years or even more than ten years to remove the pollution, which seriously threatens the surrounding environment, the health of residents and the reuse of land. Therefore, the treatment of polluted soil and groundwater has become an environmental, economic and social problem that must be faced.
[0003] At present, halogenated hydrocarbons are one of the more common organic pollutants in groundwater pollutants, among which trichloroethylene (TCE), carbon tetrachloride (CT), tetrachloroethylene (PCE) and the like are the most common. The traditional remediation technologies currently used for groundwater remediation include groundwater extraction-treatment, in-situ thermal desorption, surfactant leaching, zero-valent iron chemical reduction and other technologies. Among them, zero-valent iron has the advantages of simple preparation, long life, and no secondary pollution of the reaction products, which makes it widely used.
[0004] In recent years, nano zero-valent iron has been used as an efficient improved material for in-situ remediation of water pollution due to its superior adsorption performance, reduction activity, reaction rate and good environmental compatibility. It has been widely used in sewage treatment, contaminated soil and groundwater remediation. The nano zero-valent iron synthesized in the laboratory has a spherical structure with a core-shell dual structure. The core is solid zero-valent iron, which presents a diffusion ring structure of metallic iron body-centered cubic crystals and is surrounded by a thin oxide shell. However, it has a large specific surface area, large surface energy, fast reaction and short life. The high reaction rate and surface energy make the traditional zero-valent iron have a short reaction life; and because of its magnetic properties, it is easy to agglomerate in aqueous solution, which reduces its mobility and affects its application.
[0005] At present, in order to solve the problem of poor stability of traditional zero-valent iron and rapid reaction with water and air, reduced graphene oxide, carbon materials, carboxymethyl cellulose, oil-in-water, etc. are often used as stabilizers. Among them, carbon materials, as a cheap and easy-to-obtain good substrate material with large specific surface area and rich microporous structure, have been successfully used to stabilize and control the agglomeration of zero-valent iron, thereby enhancing its performance in environmental remediation. However, the current preparation methods are mostly step-by-step high-temperature pyrolysis, and the raw materials are mostly chemical reagents such as ferric chloride, ferrous sulfate, and sodium borohydride. The process is complicated and expensive, which limits the large-scale application of materials. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems existing in the prior art, such as poor dispersibility of zero-valent iron catalysts, easy agglomeration, and the need to further improve the remediation performance of repair materials for groundwater pollutants. An iron-based composite material and its preparation method and application are provided. The iron-based composite material modifies zero-valent iron with metal sulfides and citrates and uses carbon materials for loading, thereby improving the dispersibility of zero-valent iron and further improving the life and degradation ability of the iron-based composite material.
[0007] In order to achieve the above-mentioned objectives, the present invention provides an iron-based composite material on one hand, which includes micron-sized zero-valent iron particles, a modified shell layer formed on the surface of the micron-sized zero-valent iron particles, and a carbon material dispersed on the periphery of the micron-sized zero-valent iron particles, wherein the modified shell layer is formed by reacting metal sulfide and citrate with the micron-sized zero-valent iron particles by electrolysis.
[0008] Preferably, the particle size of the micron-sized zero-valent iron particles is 2-15 μm.
[0009] Preferably, the D of the micron-sized zero-valent iron particles is 50 The particle size is 6-12μm.
[0010] Preferably, taking the weight of the iron-based composite material as 100wt%, the content of the modified shell layer is 3.5-5.5wt%, the content of the iron of the micron-sized parts is 77-88wt%, and the content of the carbon material is 8.5-17.5wt%.
[0011] A second aspect of the present invention provides a method for preparing an iron-based composite material, the preparation method comprising the following steps:
[0012] (1) mixing micron-sized zero-valent iron with a carbon source, followed by calcination;
[0013] (2) removing the passivation film on the surface of the product obtained in step (1), and then using the product as a working electrode, the inert electrode as a counter electrode, and a solution containing metal sulfide and citrate as an electrolyte, applying power to perform constant voltage electrolysis to obtain an iron-based composite material.
[0014] Preferably, the process of step (2) includes:
[0015] S1, removing the passivation film on the surface of the product obtained in step (1) by electrolysis;
[0016] S2. Using a solution containing metal sulfide and citrate as an electrolyte, and then using the product obtained in step S1 as an anode and an inert material as a cathode to perform constant voltage electrolysis to obtain an iron-based composite material.
[0017] Preferably, in step S1, the electrolysis is performed by alternating first-stage electrolysis and second-stage electrolysis;
[0018] The product obtained in step (1) is used as a working electrode, an inert material is used as a counter electrode, and water is used as an electrolyte; the first stage of electrolysis is constant-voltage electrolysis using the inert electrode as a cathode, and the second stage of electrolysis is constant-voltage electrolysis using the inert electrode as an anode.
[0019] Preferably, in step S1, the conditions of the first stage electrolysis include: voltage of 2.5-4V, time of 30-90s;
[0020] Preferably, the conditions for the second stage electrolysis include: a voltage of 2.5-4V and a time of 30-90s.
[0021] Preferably, in step S2, the conditions for constant voltage electrolysis include: voltage of 1-2V, time of 2-5h.
[0022] Preferably, in step S1, the electrolysis time is 2-4 hours.
[0023] Preferably, the weight ratio of the micron-sized zero-valent iron particles, the metal sulfide and the citrate is 14-20:1:1.5-7.
[0024] Preferably, the particle size of the micron-sized zero-valent iron particles is 2-15 μm.
[0025] Preferably, the weight ratio of the micron-sized zero-valent iron particles to the carbon source is 1:0.05-0.5.
[0026] Preferably, the calcination conditions include: temperature of 200-250° C. and time of 5-20 min.
[0027] A third aspect of the present invention provides an iron-based composite material prepared by the above preparation method.
[0028] A fourth aspect of the present invention provides an application of the above-mentioned iron-based composite material in the remediation of groundwater pollutants.
[0029] Preferably, the groundwater pollutants are selected from one or more of carbon tetrachloride, tetrachloroethylene, trichloroethylene, dichloroethylene, tetrachloropropane and trichloropropane.
[0030] The iron-based composite material of the present invention disperses carbon materials on the periphery of micron-sized zero-valent iron particles to prevent magnetic attraction between zero-valent iron particles, thereby improving the dispersibility and stability of micron-sized zero-valent iron particles. In addition, the micron-sized zero-valent iron particles are further modified by metal sulfide and citric acid by electrochemical methods to further improve the degradation ability of micron-sized zero-valent iron particles for groundwater pollutants. In addition, the sulfide on the surface of the sulfided zero-valent iron makes the electron transfer more inclined to pollutants rather than water molecules, while inhibiting the passivation of the material, greatly improving the life and degradation ability of the iron-based composite material, and also extending the effective period of the iron-based composite material.
[0031] The present invention adopts an electrochemical method for preparing an iron-based composite material, and performs sulfurization and citric acid modification on micron-sized zero-valent iron particles by repeated alternating electrolysis between anodes and cathodes, so that the modification is more uniform and more active. In addition, the preparation method adopted by the present invention does not require the addition of catalysts such as strong acids and bases, has a simple process flow, low cost, can be recycled, and is suitable for large-scale production. More importantly, the iron-based composite material obtained by the preparation method described in this application has a better degradation effect on groundwater pollutants and has great application prospects. DETAILED DESCRIPTION
[0032] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0033] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0034] In the present invention, the passivation film on the surface of the product obtained in step (1) specifically refers to an iron oxide film generated by the surface reaction of zero-valent iron.
[0035] In the present invention, the iron-based composite material comprises micron-sized zero-valent iron particles, a modified shell layer formed on the surface of the micron-sized zero-valent iron particles, and a carbon material dispersed on the periphery of the micron-sized zero-valent iron particles, wherein the modified shell layer is formed by reacting metal sulfide and citrate with the micron-sized zero-valent iron particles by electrolysis.
[0036] In the present invention, the carbon material dispersed on the periphery of the micron-sized zero-valent iron particles is tightly connected to the micron-sized zero-valent iron through chemical bonds and is not easy to fall off. Dispersing the carbon material around the micron-sized zero-valent iron can increase the dispersibility and stability of the modified zero-valent iron, prevent the modified zero-valent iron from aggregating and causing a decrease in activity, and stabilize and control the agglomeration of zero-valent iron. In addition, the use of metal sulfide and citric acid for co-modification can make electron transfer more inclined to pollutants rather than water molecules, while inhibiting the passivation of the material, greatly improving the life and degradation ability of zero-valent iron. In the present invention, the carbon material and the modified shell layer cooperate with each other to increase the degradation ability of the iron-based composite material.
[0037] In the present invention, the carbon material may be a carbon material commonly used in the art for supporting metal particles.
[0038] In a preferred embodiment, the particle size of the micron-sized zero-valent iron particles is 2-15 μm. In the present invention, by using micron-sized zero-valent iron as an active component, the micron-sized zero-valent iron has a larger specific surface area, and its stability is stronger than that of the nano zero-valent iron used in the prior art. In the process of groundwater pollutant remediation, the remediation cycle of the material is longer and the pollutant degradation ability is better.
[0039] In a preferred embodiment, the D of the micron-sized zero-valent iron particles is 50 The particle size is 6-12μm.
[0040] In a preferred embodiment, taking the weight of the iron-based composite material as 100wt%, the content of the modified shell layer is 3.5-5.5wt%, the content of the iron of the micron-sized parts is 77-88wt%, and the content of the carbon material is 8.5-17.5wt%.
[0041] In the present invention, the micron-sized zero-valent iron is modified by using metal sulfide and citrate in an electrolytic manner, so that the modification can be more uniform and the iron-based composite material prepared later has higher activity.
[0042] In the present invention, during the electrolysis process, since the carbon material is an inert material and cannot react with metal sulfide and citrate, the distribution of the carbon material and the modified shell layer does not overlap, and the carbon material and the modified shell layer can choose to completely encapsulate the micron-sized zero-valent iron, or only partially. Further, by controlling the content of the modified shell layer and the carbon material, the activity of the iron-based composite material is improved, and the effective period of the iron-based composite material is extended.
[0043] The present invention further provides a method for preparing an iron-based composite material, the preparation method comprising the following steps:
[0044] (1) mixing micron-sized zero-valent iron particles with a carbon source, followed by calcination;
[0045] (2) removing the passivation film on the surface of the product obtained in step (1), and then using the product as a working electrode, the inert electrode as a counter electrode, and a solution containing metal sulfide and citrate as an electrolyte, applying power to perform constant voltage electrolysis to obtain an iron-based composite material.
[0046] In a specific embodiment, in step (1), the carbon material is dispersed around the zero-valent iron by mixing and calcining the zero-valent iron with a carbon source to improve the dispersibility and stability of the zero-valent iron and prevent aggregation of the zero-valent iron.
[0047] In a specific embodiment, the zero-valent iron can be a commercial product, or can be prepared by conventional methods in the art.
[0048] In a specific embodiment, the carbon source used can be a common carbon source in the art, or a common commercial product in the art. Preferably, in order to further improve the degradation performance of the prepared iron-based composite material, the carbon source is selected from one or more of gelatin, carrageenan, sodium caseinate and sodium alginate.
[0049] In a preferred embodiment, in order to further improve the degradation performance of the prepared iron-based composite material, the particle size of the selected micron-sized zero-valent iron is 2-15 μm.
[0050] In a preferred embodiment, the micron-sized zero-valent iron has a D 50 The particle size is 6-12μm.
[0051] In a specific embodiment, in step (1), when zero-valent iron and a carbon source are mixed, the carbon source may be dissolved in water first, and then the zero-valent iron is added, mixed evenly, and then dried and calcined.
[0052] In a specific embodiment, in step (1), the conditions for drying the material after mixing zero-valent iron and carbon source include: temperature of 100-120° C. and time of 30-60 min.
[0053] In a specific embodiment, in step (1), the zero-valent iron and the carbon source may be mixed by mechanical stirring at a stirring rate of 200-900 rpm, preferably 500-700 rpm.
[0054] In a preferred embodiment, in order to further improve the degradation performance of the prepared iron-based composite material, the weight ratio of the zero-valent iron to the carbon source is controlled to be 1:0.05-0.5, preferably 1:0.1-0.3. Specifically, the weight ratio of the zero-valent iron to the carbon source can be 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4 or 1:0.5.
[0055] In a preferred embodiment, in step (1), the calcination conditions include: a temperature of 200-250°C and a time of 5-20 min. Specifically, the calcination temperature may be 200°C, 210°C, 220°C, 230°C, 240°C or 250°C; and the calcination time may be 5 min, 10 min, 15 min or 20 min.
[0056] In the present invention, an electrochemical method is used to modify zero-valent iron with metal sulfide and citric acid, thereby further improving the degree of modification, thereby improving the degree of modification of zero-valent iron in the iron-based composite material, and further improving the ability of the iron-based composite material to degrade pollutants.
[0057] In a specific embodiment, before the electrochemical modification in step (2), it is necessary to first remove the passivation film on the surface of the zero-valent iron in the product obtained in step (1) to increase the number and reaction activity of active sites on the surface of the zero-valent iron, so as to facilitate the subsequent modification of the zero-valent iron using metal sulfides and citrates.
[0058] In the present invention, the method for removing the passivation film on the surface of the product obtained in step (1) is not limited, as long as the passivation film on the surface of the material can be removed.
[0059] In a preferred embodiment, the process of step (2) comprises:
[0060] S1, removing the passivation film on the surface of the product obtained in step (1) by electrolysis;
[0061] S2. Using a solution containing metal sulfide and citrate as an electrolyte, and then using the product obtained in step S1 as an anode and an inert material as a cathode to perform constant voltage electrolysis to obtain an iron-based composite material.
[0062] In a preferred embodiment, in order to improve the removal rate of the passivation film on the surface of the product prepared in step (1) and ensure the uniformity of the subsequent modification, etc., electrolytic removal can be selected.
[0063] In a preferred embodiment, in step S1, the electrolysis is performed by alternating first-stage electrolysis and second-stage electrolysis;
[0064] The product obtained in step (1) is used as a working electrode, an inert material is used as a counter electrode, and water is used as an electrolyte; the first stage of electrolysis is constant-voltage electrolysis using the inert electrode as a cathode, and the second stage of electrolysis is constant-voltage electrolysis using the inert electrode as an anode.
[0065] In a preferred embodiment, the product obtained in step (1) can be used as a working electrode, and then the passivation film on the surface of the product obtained in step (1) can be removed by repeated alternating electrolysis of the anode and cathode, so that the subsequent modification of the zero-valent iron is more uniform, and the degradation performance of the prepared iron-based composite material is further improved.
[0066] In a specific embodiment, in step S1, the choice of the first electrolysis is not limited when the first-stage electrolysis and the second-stage electrolysis are performed alternately. It can be understood that in the process of alternating electrolysis, the first electrolysis is not limited to the first-stage electrolysis or the second-stage electrolysis, and it is only required that the subsequent first-stage electrolysis and the second-stage electrolysis are performed alternately.
[0067] In the present invention, in the first stage of electrolysis, oxygen is produced by electrolyzing water in the anode region, so that the passivation film layer on the surface of zero-valent iron is gradually mechanically destroyed. At the same time, H + The dissolution of the passivation film can be further promoted, and the passivation film layer on the surface of the zero-valent iron can be further removed. In the second stage of electrolysis, a large amount of hydrogen is generated by electrolyzing water in the cathode area, which causes the passivation film layer to be further and gradually mechanically destroyed. By alternating the first stage electrolysis and the second stage electrolysis, it is ensured that the passivation film layer on the surface of the zero-valent iron is removed as much as possible. And the removal by electrolysis can also avoid the problems such as solvent contamination caused by the removal of the passivation film layer by strong acid and strong alkali commonly used in the prior art, and is suitable for large-scale production, and the preparation process does not introduce secondary pollution.
[0068] In the present invention, in step S1, the conditions of the first stage electrolysis include: a voltage of 2.5-4V, preferably 2.6-3.5V, and a time of 30-90s, preferably 40-60s. Specifically, the voltage of the first stage electrolysis can be 2.5V, 3V, 3.5V or 4V; and the time of the first stage electrolysis can be 30s, 40s, 50s, 60s, 70s, 80s or 90s.
[0069] In the present invention, in step S1, the conditions of the second stage electrolysis include: a voltage of 2.5-4V, preferably 2.6-3.5V, and a time of 30-90s, preferably 40-60s. Specifically, the voltage of the second stage electrolysis can be 2.5V, 3V, 3.5V or 4V; and the time of the second stage electrolysis can be 30s, 40s, 50s, 60s, 70s, 80s or 90s.
[0070] In a specific embodiment, the voltage and electrolysis time set for the first stage electrolysis may be the same or different from the voltage and electrolysis time set for the second stage electrolysis. Preferably, the voltage and electrolysis time set for the first stage electrolysis are the same as the voltage and electrolysis time set for the second stage electrolysis.
[0071] In a specific embodiment, in step S1, the total time for alternating the first stage electrolysis and the second stage electrolysis is not limited. It is only necessary to remove the passivation film on the surface of the product obtained in step (1) by alternating the first stage electrolysis and the second stage electrolysis.
[0072] In a preferred embodiment, in order to further ensure that the passivation film on the surface of the product obtained in step (1) is completely removed, in step S1, the electrolysis time is 2-4 hours. Specifically, the electrolysis time can be 2 hours, 3 hours or 4 hours. The electrolysis time in step S1 refers to the total electrolysis time of alternating the first stage electrolysis and the second stage electrolysis.
[0073] In a specific embodiment, after the electrolysis in step S1 is completed, in order to further save preparation time, it is possible to choose not to replace the electrolytic cell, and directly add metal sulfide and citrate to the electrolytic cell used in step S1 to obtain the electrolyte required for step S2.
[0074] In the present invention, in step S2, the product obtained after electrolysis in step S1 is used as an anode, and metal sulfide and citrate are added to the original electrolyte (water) to achieve modification of zero-valent iron during the electrolysis process. The zero-valent iron modified by the method described in the present invention is more uniformly modified, and the degradation ability of the obtained product is better.
[0075] In the present invention, in step S2, the pH value of the electrolyte needs to be monitored at any time during the electrolysis process, and the electrolyte is controlled to be an alkaline environment to ensure that sodium sulfide and sodium citrate exist in the electrolyte in the form of anions. When the pH value of the electrolyte is 7-8, the power is stopped to obtain the iron-based composite material.
[0076] In a preferred embodiment, in step S2, the conditions of the constant voltage electrolysis include: a voltage of 1-2V and a time of 2-5h. Specifically, the voltage of the constant voltage electrolysis is 1V, 1.5V or 2V; and the time of the constant voltage electrolysis is 2h, 3h, 4h or 5h.
[0077] In a preferred embodiment, the weight ratio of the micron-sized zero-valent iron particles, the metal sulfide and the citrate is 14-20:1:1.5-7, more preferably 14-20:1:2-6.
[0078] In a preferred embodiment, in step S2, the metal sulfide is sodium sulfide and / or potassium sulfide, and the citrate is selected from one or more of sodium citrate, potassium citrate, magnesium citrate and ferric citrate.
[0079] In a preferred embodiment, the concentration of metal sulfide in the electrolyte is controlled to be 0.6-1.5 mol / L, and the concentration of citrate in the electrolyte is controlled to be 0.6-1.5 mol / L.
[0080] In a specific embodiment, in step (2), after the electrolysis is completed, the obtained product needs to be washed with pure water for 2-5 times and then dried at low temperature under inert atmosphere to obtain an iron-based composite material.
[0081] In the present invention, during the first-stage electrolysis, the second-stage electrolysis and the constant-voltage electrolysis in step S2, the electrolytic cell selected may be an electrolytic cell with a cathode region and an anode region commonly used in the art, and a diaphragm is used to separate the cathode region and the anode region to avoid mutual influence between substances obtained by electrolysis in the cathode region and the anode region.
[0082] In a specific embodiment, in steps S1 and S2, when the product obtained in step (1) is modified as a working electrode, the product obtained in step (1), carbon black and nafion adhesive can be evenly mixed, and then the slurry is coated on a graphite plate and dried as a working electrode.
[0083] The present invention can further provide an application of the iron-based composite material in the remediation of groundwater pollutants.
[0084] In the present invention, the iron-based composite material can be directly injected into groundwater to treat pollutants, and can also be used as a reducing agent in a permeable reaction wall to directly treat pollutants.
[0085] In a specific embodiment, when the iron-based composite material is used to treat groundwater pollutants, the type of groundwater to be treated is not limited. The iron-based composite material of the present invention is particularly suitable for groundwater with high dissolved oxygen and nitrate content, and can quickly reduce the redox potential of the groundwater, form a reducing environment, and ensure that the zero-valent iron surface loses some of its reducing ability due to the oxidation of oxygen and nitrate as much as possible.
[0086] In a preferred embodiment, the groundwater pollutant is selected from one or more of carbon tetrachloride, tetrachloroethylene, trichloroethylene, dichloroethylene, tetrachloropropane and trichloropropane. The iron-based composite material of the present invention has excellent degradation ability for these pollutants.
[0087] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0088] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0089] In the following examples and comparative examples, in step (2), the working electrode is prepared by mixing the product obtained in step (1), carbon black, and nafion binder in a weight ratio of 8:1:1 to form a slurry, and then coating the slurry on a 1×1 cm 2 After drying on a graphite plate, it was used as a working electrode.
[0090] Example 1
[0091] (1) Dissolve carrageenan in water and then add zero-valent iron particles (the weight ratio of carrageenan to zero-valent iron particles is 0.1:1, and the D 50 The particle size is 7 μm), the mixture is mixed evenly with mechanical stirring (stirring rate 600 rpm) and dried at 110° C. for 40 min, and then the dried material is placed in a muffle furnace for calcination at a calcination temperature of 220° C. and a calcination time of 8 min;
[0092] (2) The product obtained in step (1) is subjected to first-stage electrolysis and second-stage electrolysis alternately, with a total electrolysis time of 2 h; wherein the product obtained in step (1) is used as a working electrode, a carbon rod is used as a counter electrode, and water is used as an electrolyte; the first-stage electrolysis is performed by using the carbon rod electrode as a cathode for constant-voltage electrolysis, with a voltage of 2.5 V and a time of 60 s; the second-stage electrolysis is performed by using the carbon rod as an anode for constant-voltage electrolysis, with a voltage of 2.5 V and a time of 60 s;
[0093] (3) 1 mol / L sodium sulfide and 1 mol / L sodium citrate were added to the electrolyte (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate was 20:1:2), and then the product obtained in step (2) was used as an anode and a carbon rod was used as a cathode to perform constant voltage electrolysis at a voltage of 1.5 V for an electrolysis time of 2 h. After the electrolysis was completed, the iron-based composite material was washed with pure water for 2-5 times and then dried. XPS detection showed that in the iron-based composite material, the content of the modified shell was 4.9 wt%, the content of the micron-sized zero-valent iron was 85.8 wt%, and the content of the carbon material was 9.3 wt%.
[0094] Example 2
[0095] (1) Sodium alginate was dissolved in water, and then zero-valent iron particles were added (the weight ratio of sodium alginate to zero-valent iron particles was 0.15:1, and the D 50 The particle size is 8 μm), the mixture is mixed by mechanical stirring (stirring rate is 700 rpm) and then dried at 110°C for 30 min, and then the dried material is placed in a muffle furnace for calcination at a calcination temperature of 210°C and a calcination time of 10 min;
[0096] (2) The product obtained in step (1) is subjected to first-stage electrolysis and second-stage electrolysis alternately, with a total electrolysis time of 2.5 h; wherein the product obtained in step (1) is used as a working electrode, a carbon rod is used as a counter electrode, and water is used as an electrolyte; the first-stage electrolysis is performed by using the carbon rod electrode as a cathode for constant-voltage electrolysis, with a voltage of 2.8 V and a time of 60 s; the second-stage electrolysis is performed by using the carbon rod as an anode for constant-voltage electrolysis, with a voltage of 2.8 V and a time of 60 s;
[0097] (3) 1.1 mol / L sodium sulfide and 1.1 mol / L sodium citrate were added to the electrolyte (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate was 16.6:1:3), and then the product obtained in step (2) was used as an anode and a carbon rod was used as a cathode to perform constant voltage electrolysis at a voltage of 1.6 V for an electrolysis time of 2.5 h. After the electrolysis, the iron-based composite material was washed with pure water for 2-5 times and then dried. XPS detection showed that in the iron-based composite material, the content of the modified shell was 5.1 wt%, the content of the micron-sized zero-valent iron was 83.2 wt%, and the content of the carbon material was 11.7 wt%.
[0098] Example 3
[0099] (1) Sodium caseinate was dissolved in water, and then zero-valent iron particles were added (the weight ratio of sodium caseinate to zero-valent iron was 0.2:1, and the D 50 The particle size is 6 μm), the mixture is mixed evenly by mechanical stirring (stirring rate is 700 rpm), and then dried at 120° C. for 40 min. The dried material is then placed in a muffle furnace for calcination at a temperature of 220° C. for 8 min.
[0100] (2) The product obtained in step (1) is subjected to first-stage electrolysis and second-stage electrolysis alternately, with a total electrolysis time of 3 h; wherein the product obtained in step (1) is used as a working electrode, a carbon rod is used as a counter electrode, and water is used as an electrolyte; the first-stage electrolysis is performed by using the carbon rod electrode as a cathode for constant-voltage electrolysis, with a voltage of 3 V and a time of 45 s; the second-stage electrolysis is performed by using the carbon rod as an anode for constant-voltage electrolysis, with a voltage of 3 V and a time of 45 s;
[0101] (3) 1.2 mol / L sodium sulfide and 1.2 mol / L sodium citrate were added to the electrolyte (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate was 16.6:1:6), and then the product obtained in step (2) was used as an anode and a carbon rod was used as a cathode to perform constant voltage electrolysis at a voltage of 1.7 V for 3 h. After the electrolysis was completed, the iron-based composite material was washed with pure water for 2-5 times and then dried. XPS detection showed that in the iron-based composite material, the content of the modified shell was 5 wt%, the content of the micron-sized zero-valent iron was 81.8 wt%, and the content of the carbon material was 13.2 wt%.
[0102] Example 4
[0103] (1) Dissolve carrageenan in water and then add zero-valent iron particles (the weight ratio of carrageenan to zero-valent iron particles is 0.25:1, and the D 50 The particle size is 5 μm), mechanically stirred (stirring rate 700 rpm) to mix evenly and then dried at 120 ° C for 30 min, and then the dried material is placed in a muffle furnace for calcination at a calcination temperature of 230 ° C and a calcination time of 10 min;
[0104] (2) The product obtained in step (1) is subjected to first-stage electrolysis and second-stage electrolysis alternately, with a total electrolysis time of 3.5 h; wherein the product obtained in step (1) is used as a working electrode, a carbon rod is used as a counter electrode, and water is used as an electrolyte; the first-stage electrolysis is performed by using the carbon rod electrode as a cathode for constant-voltage electrolysis, with a voltage of 3.2 V and a time of 45 s; the second-stage electrolysis is performed by using the carbon rod as an anode for constant-voltage electrolysis, with a voltage of 3.2 V and a time of 45 s;
[0105] (3) adding 0.8 mol / L sodium sulfide and 0.8 mol / L sodium citrate to the electrolyte (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate is 16.6:1:4), then using the product obtained in step (2) as an anode and a carbon rod as a cathode, and performing constant voltage electrolysis at a voltage of 1.8 V for an electrolysis time of 3.5 h. After the electrolysis, washing with pure water for 2-5 times and drying to obtain an iron-based composite material; XPS detection showed that in the iron-based composite material, the content of the modified shell was 4.8 wt%, the content of the micron-sized zero-valent iron was 79.2 wt%, and the content of the carbon material was 16 wt%.
[0106] Example 5
[0107] (1) Gelatin was dissolved in water, and then zero-valent iron particles were added (the weight ratio of gelatin to zero-valent iron was 0.3:1, and the D 50The particle size is 8 μm), the mixture is mixed evenly by mechanical stirring (stirring rate is 700 rpm), and then dried at 120° C. for 40 min. The dried material is then placed in a muffle furnace for calcination at a temperature of 220° C. for 10 min.
[0108] (2) The product obtained in step (1) is subjected to first-stage electrolysis and second-stage electrolysis alternately, with a total electrolysis time of 4 hours; wherein the product obtained in step (1) is used as a working electrode, a carbon rod is used as a counter electrode, and water is used as an electrolyte; the first-stage electrolysis is performed by using the carbon rod electrode as a cathode for constant-voltage electrolysis, with a voltage of 3.5 V and a time of 50 seconds; the second-stage electrolysis is performed by using the carbon rod as an anode for constant-voltage electrolysis, with a voltage of 3.5 V and a time of 50 seconds;
[0109] (3) 1.5 mol / L sodium sulfide and 1.5 mol / L sodium citrate were added to the electrolyte (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate was 14.2:1:5), and then the product obtained in step (2) was used as an anode and a carbon rod was used as a cathode to perform constant voltage electrolysis at a voltage of 2 V for 4 h. After the electrolysis, the iron-based composite material was washed with pure water for 2-5 times and then dried. XPS detection showed that the content of the modified shell in the iron-based composite material was 4.5 wt%, the content of micron-sized zero-valent iron was 81.2 wt%, and the content of the carbon material was 14.3 wt%.
[0110] Example 6
[0111] (1) Dissolve carrageenan in water and then add zero-valent iron particles (the weight ratio of carrageenan to zero-valent iron particles is 0.6:1, and the D 50 The particle size is 7 μm), the mixture is mixed evenly with mechanical stirring (stirring rate 600 rpm) and dried at 110° C. for 40 min, and then the dried material is placed in a muffle furnace for calcination at a calcination temperature of 220° C. and a calcination time of 8 min;
[0112] (2) The product obtained in step (1) is subjected to first-stage electrolysis and second-stage electrolysis alternately, with a total electrolysis time of 2 h; wherein the product obtained in step (1) is used as a working electrode, a carbon rod is used as a counter electrode, and water is used as an electrolyte; the first-stage electrolysis is performed by using the carbon rod electrode as a cathode for constant-voltage electrolysis, with a voltage of 2.5 V and a time of 60 s; the second-stage electrolysis is performed by using the carbon rod as an anode for constant-voltage electrolysis, with a voltage of 2.5 V and a time of 60 s;
[0113] (3) 1 mol / L sodium sulfide and 1 mol / L sodium citrate were added to the electrolyte (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate was 20:1:2), and then the product obtained in step (2) was used as an anode and a carbon rod was used as a cathode to perform constant voltage electrolysis at a voltage of 1.5 V for an electrolysis time of 2 h. After the electrolysis was completed, the iron-based composite material was washed with pure water for 2-5 times and then dried. XPS detection showed that in the iron-based composite material, the content of the modified shell was 1.8 wt%, the content of the micron-sized zero-valent iron was 79.3 wt%, and the content of the carbon material was 18.9 wt%.
[0114] Example 7
[0115] (1) Dissolve carrageenan in water and then add zero-valent iron particles (the weight ratio of carrageenan to zero-valent iron particles is 0.1:1, and the D 50 The particle size is 7 μm), the mixture is mixed evenly with mechanical stirring (stirring rate 600 rpm) and dried at 110° C. for 40 min, and then the dried material is placed in a muffle furnace for calcination at a calcination temperature of 220° C. and a calcination time of 8 min;
[0116] (2) The product obtained in step (1) is subjected to first-stage electrolysis and second-stage electrolysis alternately, with a total electrolysis time of 2 h; wherein the product obtained in step (1) is used as a working electrode, a carbon rod is used as a counter electrode, and water is used as an electrolyte; the first-stage electrolysis is performed by using the carbon rod electrode as a cathode for constant-voltage electrolysis, with a voltage of 2.5 V and a time of 60 s; the second-stage electrolysis is performed by using the carbon rod as an anode for constant-voltage electrolysis, with a voltage of 2.5 V and a time of 60 s;
[0117] (3) 1 mol / L sodium sulfide and 1 mol / L sodium citrate were added to the electrolyte (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate was 20:1:2), and then the product obtained in step (2) was used as an anode and a carbon rod was used as a cathode to perform constant voltage electrolysis at a voltage of 2.5 V for an electrolysis time of 2 h. After the electrolysis was completed, the iron-based composite material was washed with pure water for 2-5 times and then dried. XPS detection showed that in the iron-based composite material, the content of the modified shell was 5.8 wt%, the content of the micron-sized zero-valent iron was 84.2 wt%, and the content of the carbon material was 10 wt%.
[0118] Example 8
[0119] (1) Dissolve carrageenan in water and then add zero-valent iron particles (the weight ratio of carrageenan to zero-valent iron particles is 0.1:1, and the D 50 The particle size is 7 μm), the mixture is mixed evenly with mechanical stirring (stirring rate 600 rpm) and dried at 110° C. for 40 min, and then the dried material is placed in a muffle furnace for calcination at a calcination temperature of 220° C. and a calcination time of 8 min;
[0120] (2) The product obtained in step (1) is subjected to first-stage electrolysis and second-stage electrolysis alternately, with a total electrolysis time of 2 h; wherein the product obtained in step (1) is used as a working electrode, a carbon rod is used as a counter electrode, and water is used as an electrolyte; the first-stage electrolysis is performed by using the carbon rod electrode as a cathode for constant-voltage electrolysis, with a voltage of 2.5 V and a time of 60 s; the second-stage electrolysis is performed by using the carbon rod as an anode for constant-voltage electrolysis, with a voltage of 2.5 V and a time of 60 s;
[0121] (3) 1 mol / L sodium sulfide and 1 mol / L sodium citrate were added to the electrolyte (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate was 20:1:10), and then the product obtained in step (2) was used as an anode and a carbon rod was used as a cathode to perform constant voltage electrolysis at a voltage of 1.5 V for an electrolysis time of 2 h. After the electrolysis was completed, the iron-based composite material was washed with pure water for 2-5 times and then dried. XPS detection showed that in the iron-based composite material, the content of the modified shell was 7.1 wt%, the content of the micron-sized zero-valent iron was 75.6 wt%, and the content of the carbon material was 17.3 wt%.
[0122] Example 9
[0123] (1) Dissolve carrageenan in water and then add zero-valent iron particles (the weight ratio of carrageenan to zero-valent iron particles is 0.1:1, and the D 50 The particle size is 7 μm), the mixture is mixed evenly with mechanical stirring (stirring rate 600 rpm) and dried at 110° C. for 40 min, and then the dried material is placed in a muffle furnace for calcination at a calcination temperature of 220° C. and a calcination time of 8 min;
[0124] (2) The product obtained in step (1) is subjected to first-stage electrolysis and second-stage electrolysis alternately, with a total electrolysis time of 2 h; wherein the product obtained in step (1) is used as a working electrode, a carbon rod is used as a counter electrode, and water is used as an electrolyte; the first-stage electrolysis is performed by using the carbon rod electrode as a cathode for constant-voltage electrolysis, with a voltage of 2.5 V and a time of 60 s; the second-stage electrolysis is performed by using the carbon rod as an anode for constant-voltage electrolysis, with a voltage of 2.5 V and a time of 60 s;
[0125] (3) 1 mol / L sodium sulfide and 1 mol / L sodium citrate were added to the electrolyte (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate was 25:1:2), and then the product obtained in step (2) was used as an anode and a carbon rod was used as a cathode to perform constant voltage electrolysis at a voltage of 1.5 V for an electrolysis time of 2 h. After the electrolysis was completed, the iron-based composite material was washed with pure water for 2-5 times and then dried. XPS detection showed that in the iron-based composite material, the content of the modified shell was 3.3 wt%, the content of the micron-sized zero-valent iron was 89.3 wt%, and the content of the carbon material was 7.4 wt%.
[0126] Example 10
[0127] (1) Dissolve carrageenan in water and then add zero-valent iron particles (the weight ratio of carrageenan to zero-valent iron particles is 0.1:1, and the D 50 The particle size is 7 μm), the mixture is mixed evenly with mechanical stirring (stirring rate 600 rpm) and dried at 110° C. for 40 min, and then the dried material is placed in a muffle furnace for calcination at a calcination temperature of 220° C. and a calcination time of 8 min;
[0128] (2) soaking the product obtained in step (1) in a 1 mol / L HCl solution for 15 min, taking it out after soaking and washing it with water;
[0129] (3) 1 mol / L sodium sulfide and 1 mol / L sodium citrate were added to the electrolyte (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate was 20:1:2), and then the product obtained in step (2) was used as an anode and a carbon rod was used as a cathode to perform constant voltage electrolysis at a voltage of 1.5 V for an electrolysis time of 2 h. After the electrolysis was completed, the iron-based composite material was washed with pure water for 2-5 times and then dried. XPS detection showed that in the iron-based composite material, the content of the modified shell was 2.1 wt%, the content of the micron-sized zero-valent iron was 85.4 wt%, and the content of the carbon material was 12.5 wt%.
[0130] Comparative Example 1
[0131] Sodium caseinate was dissolved in water, and then zero-valent iron particles were added (the weight ratio of sodium caseinate to zero-valent iron was 0.2:1, and the D 50 The particle size is 9 μm), mechanically stirred (stirring rate 700 rpm) to mix evenly and then dried at 120° C. for 40 min, and then the dried material is placed in a muffle furnace for calcination at a calcination temperature of 220° C. and a calcination time of 8 min to obtain the product.
[0132] Comparative Example 2
[0133] (1) Zero-valent iron particles (D 50 The first and second stages of electrolysis were performed alternately, with a total electrolysis time of 3 h. The zero-valent iron particles were used as working electrodes, the carbon rods were used as counter electrodes, and water was used as electrolyte. The first stage of electrolysis was performed by using the carbon rod electrode as the cathode for constant voltage electrolysis at a voltage of 2.5 V for 60 s. The second stage of electrolysis was performed by using the carbon rod as the anode for constant voltage electrolysis at a voltage of 2.5 V for 60 s.
[0134] (2) 1 mol / L sodium sulfide and 1 mol / L sodium citrate (the weight ratio of zero-valent iron particles, sodium sulfide and sodium citrate is 20:1:2) are added to the electrolyte, and then the product obtained in step (1) is used as the anode and the carbon rod is used as the cathode to perform constant voltage electrolysis at a voltage of 1.5 V for an electrolysis time of 2 h. After completion, the product is washed with pure water for 2-5 times and then dried to obtain the product.
[0135] Test Case
[0136] Test Example 1
[0137] The particle size distribution of the iron-based composite materials prepared in Examples 1-5 was tested using a laser particle size analyzer, and it was found that the particle size of the iron-based composite materials was 3-18 μm.
[0138] Test Example 2
[0139] The iron-based composite materials prepared in Examples 1-5 and the product prepared in Comparative Example 1 were tested by XRD. According to the results of XRD, the iron in the iron-based composite materials prepared in Examples 1-5 was elemental iron, and there was no iron oxide, indicating that the passivation film on the surface of the product prepared in the present invention was completely removed, and the product prepared in Comparative Example 1 contained not only elemental iron but also iron oxide;
[0140] In addition, the iron-based composite materials prepared in Examples 1-5 were left to stand for 12 months and then tested again by XRD. It was found that the characteristic peaks of zero-valent iron still existed in the XRD spectra of the products prepared in Examples 1-5, indicating that the iron-based composite materials prepared by the method of the present invention had strong stability, and the modification of zero-valent iron was relatively uniform, which reduced the probability of oxidation passivation of zero-valent iron.
[0141] The product prepared in Comparative Example 1 was left to stand for 3 months and then tested again by XRD. It can be seen that the intensity of the characteristic peak of iron oxide in its spectrum increased, indicating that the stability of the product prepared in Comparative Example 1 was poor;
[0142] According to the full element scan of XPS, in addition to Fe element, the products prepared in Examples 1-10 also contain Na element, S element and C element. The product prepared in Comparative Example 1 does not contain Na element and S element, and the product prepared in Comparative Example 2 does not contain C element, indicating that zero-valent iron is successfully modified by electrochemical means in the present invention.
[0143] Test Example 3
[0144] The products prepared in Examples 1-10 and Comparative Examples 1-2 were subjected to a static sustained-release test;
[0145] Test method: Take 1g of the sample to be tested and place it in 100mL of boiled and cooled water, let it stand for 12 months, then perform XRD test, and analyze the obtained XRD spectrum to obtain the content of elemental iron in the sample. The results are shown in Table 1.
[0146] Test Example 4
[0147] The degradation ability of the products prepared in Examples 1-10 and Comparative Examples 1-2 for chlorinated hydrocarbon pollutants was tested;
[0148] Test method: The products prepared in Examples 1-10 and Comparative Examples 1-2 were mixed with simulated chlorinated hydrocarbon contaminated groundwater samples (the types and concentrations of pollutants in the simulated samples are shown in Table 1) for reaction at a reaction temperature of 15-20°C and a reaction time of 12 hours. The concentration of chlorinated hydrocarbons after the reaction was tested, and the degradation rate of chlorinated hydrocarbons was calculated using the formula: (chlorinated hydrocarbon concentration before reaction - chlorinated hydrocarbon concentration after reaction) ÷ chlorinated hydrocarbon concentration before reaction × 100%; the results are shown in Table 1.
[0149] Table 1
[0150]
[0151]
[0152] It can be seen from the results in Table 1 that the iron-based composite material of the present invention has excellent degradation performance against chlorinated hydrocarbons, and a more durable repair cycle, and the preparation method is simple, green and pollution-free, and has great application prospects.
[0153] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An iron-based composite material, characterized in that: The iron-based composite material includes micron-sized zero-valent iron particles, a modified shell layer formed on the surface of the micron-sized zero-valent iron particles, and a carbon material dispersed around the periphery of the micron-sized zero-valent iron particles, wherein the modified shell layer is formed by reacting metal sulfide and citrate with the micron-sized zero-valent iron particles by electrolysis.
2. The iron-based composite material according to claim 1, characterized in that: The particle size of the micron-sized zero-valent iron particles is 2-15 μm; Preferably, the D of the micron-sized zero-valent iron particles is 50 The particle size is 6-12μm.
3. The iron-based composite material according to claim 1, characterized in that: Taking the weight of the iron-based composite material as 100wt%, the content of the modified shell layer is 3.5-5.5wt%, the content of the iron in the micron-sized parts is 77-88wt%, and the content of the carbon material is 8.5-17.5wt%.
4. A method for preparing an iron-based composite material, characterized in that: The preparation method comprises the following steps: (1) mixing micron-sized zero-valent iron particles with a carbon source, followed by calcination; (2) removing the passivation film on the surface of the product obtained in step (1), and then using the product as a working electrode, the inert electrode as a counter electrode, and a solution containing metal sulfide and citrate as an electrolyte, applying power to perform constant voltage electrolysis to obtain an iron-based composite material.
5. The method for preparing the iron-based composite material according to claim 4, characterized in that: The process of step (2) includes: S1, removing the passivation film on the surface of the product obtained in step (1) by electrolysis; S2. Using a solution containing metal sulfide and citrate as an electrolyte, and then using the product obtained in step S1 as an anode and an inert material as a cathode to perform constant voltage electrolysis to obtain an iron-based composite material.
6. The method for preparing the iron-based composite material according to claim 5, characterized in that: In step S1, the electrolysis is performed by alternating the first stage electrolysis and the second stage electrolysis; The product obtained in step (1) is used as a working electrode, an inert material is used as a counter electrode, and water is used as an electrolyte; the first stage of electrolysis is constant-voltage electrolysis using the inert electrode as a cathode, and the second stage of electrolysis is constant-voltage electrolysis using the inert electrode as an anode.
7. The method for preparing the iron-based composite material according to claim 6, characterized in that: In step S1, the conditions of the first stage electrolysis include: voltage of 2.5-4V, time of 30-90s; Preferably, the conditions for the second stage electrolysis include: a voltage of 2.5-4V and a time of 30-90s.
8. The method for preparing the iron-based composite material according to claim 5, characterized in that: In step S2, the conditions of constant voltage electrolysis include: voltage of 1-2V, time of 2-5h.
9. The method for preparing the iron-based composite material according to claim 5, characterized in that: In step S1, the electrolysis time is 2-4 hours.
10. The method for preparing the iron-based composite material according to claim 4 or 5, characterized in that: The weight ratio of the micron-sized zero-valent iron particles, the metal sulfide and the citrate is 14-20:1:1.5-7.
11. The method for preparing the iron-based composite material according to claim 4, characterized in that: The particle size of the micron-sized zero-valent iron particles is 2-15 μm.
12. The method for preparing the iron-based composite material according to claim 4, characterized in that: The weight ratio of the micron-sized zero-valent iron particles to the carbon source is 1:0.05-0.
5.
13. The method for preparing the iron-based composite material according to claim 4, characterized in that: The calcination conditions include: temperature of 200-250° C. and time of 5-20 min.
14. The iron-based composite material prepared according to the method for preparing the iron-based composite material according to any one of claims 4 to 13.
15. Use of the iron-based composite material according to any one of claims 1 to 3 or the iron-based composite material according to claim 14 in the remediation of groundwater pollutants.
16. The use according to claim 15, characterized in that The groundwater pollutants are selected from one or more of carbon tetrachloride, tetrachloroethylene, trichloroethylene, dichloroethylene, tetrachloropropane and trichloropropane.
Citation Information
Patent Citations
Sulfated / citrate cooperative modified micrometer zero-valent iron material and preparation method and application thereof
CN109796070A
Preparation method and application of slow-release micro-nano zero-valent iron material
CN114713226A
Method for improving reductive decontamination efficiency of nanoscale zero-valent iron in aerobic water
CN114890529A
A modified carbon-based material, its preparation method and application
CN114937781A
Biochar-loaded vulcanized nano zero-valent iron as well as preparation method and application thereof
CN115650354A
Cited By
Improved groundwater remediation agent and preparation method thereof
CN120622647A
An improved groundwater remediation agent and its preparation method
CN120622647B